Protection of minor rights in Russia and European Union countries - Vyacheslav, Bocharov A.; Fedotova, Olga A.; Kakurina, Marina V.; Mikhaleva, Galia G.; Novikova, Svetlana V. (Linguistics and Culture Review, 2021)
The goal of the study is to develop the problem of minor rights and legitimate interest protection theoretically. Discussion: A comprehensive analysis of the system for protection the rights of this category of citizens was carried out to achieve this goal. At the same time, special attention is paid to the basic concepts and approaches used for the implementation of the studied legal relations in Russia and the EU countries. Result: they revealed the features of minor right protection system in the Russian Federation and some EU states.